Disparities by race, age, and sex in the improvement of survival for lymphoma: Findings from a population-based study. - Fahad Mukhtar; Paolo Boffetta; Bashir Dabo; Jong Y Park; Chi T D Tran; Thuan V Tran; Huong Thi-Thanh Tran; Madison Whitney; Harvey A Risch; Linh C Le; Wei Zheng; Xiao-Ou Shu; et al. (PLoS ONE)
Objective To evaluate improvement in survival of lymphoma patients from 1990 to 2014, stratified by age, sex and race using Surveillance Epidemiology and End-Result Survey Program (SEER) data. Study design and setting We identified 113,788 incident lymphoma cases from nine SEER cancer registries were followed up for cause-specific mortality from lymphoma. Cox proportional hazard regression was used to estimate hazard ratios (HRs) and their respective 95% confidence interval (CIs) for various time periods within groups stratified by race, age and sex. Results Five-year survival for Hodgkin's lymphoma (HL) was 89% for patients 20-49 years of age. For this age group, compared to 1990-1994, survival significantly improved in 2000-2004 (HR = 0.65; 95% CI: 0.54-0.78), 2005-2009 (HR = 0.46, 95% CI: 0.38-0.57) and 2010-2014 (HR = 0.29, 95% CI: 0.20-0.41). Hodgkin's lymphoma patients aged 75-85 years had 5-year survival of 37% and in these patients, compared to 1990-1994, survival only improved from 2005 onward (HR = 0.67, 95% CI: 0.50-0.90). In patients with non-Hodgkin's Lymphoma (NHL), all age groups showed survival improvements between 1990-1994 period and 2010-2014 period. Improvements in HL and NHL survival were seen for all race categories and both genders. Conclusion Survival among US lymphoma patients has improved substantially between 1990-1994 period and 2010-2014 period, though disease-specific mortality was still higher in older age groups.